Antibacterial activities of essential oils from Iranian medicinal plants on extended-spectrum Î²-lactamase-producing Escherichia coli - Sharifi-Rad, J; Mnayer, D; Roointan, A; Shahri, F; Ayatollahi, S A M; Sharifi-Rad, M; Molaee, N; Sharifi-Rad, M (Cellular and Molecular Biology, 2016)
The extended-spectrum beta-lactamase (ESBL) -producing Escherichia coli strains can lead to various infections particularly urinary tract infections. The main objective of this investigation was to evaluate the antibacterial activities of essential oils (EOs) from different Iranian medicinal plants against TEM gene positive ESBL-producing E. coli strains isolated from urine samples of patients with urinary tract infections. EOs were extracted using hydrodistillation method. E. coli strains were isolated by different specific Medias. ESBL-producing E. coli strains were isolated from urine samples of patients with urinary tract infections in Shiraz hospital, Iran. Then, ESBL- producing strains were identified using double disk synergy test, phenotypic disc confirmatory test and polymerase chain reaction (PCR) for TEM gene detection. The antibacterial activity of the EOs from different plants (Achillea wilhelmsii C. Koch, Echinophora platyloba DC., Lallemantia royleana, Nepeta persica Boiss., Pulicaria vulgaris Gaertn., Salvia nemorosa, and Satureja intermedia C.A.Mey) and antibiotics against ESBL-producing strains was studied using the microdilution method for the evaluation of the minimum inhibitory concentration (MIC). The 103 out of 295 E. coli strains with 97 (90.65%) TEM gene distributions were identified as ESBL-producing strains. All of the EOs derived from different plants displayed high inhibitory effects against ESBL-producing E. coli strains. The results of our investigations may propose a good treatment option against resistant infectious bacteria.